2014
DOI: 10.1108/tg-01-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

E-government implementation in Zambia – prospects

Abstract: Purpose – The article aims to investigate the potential of successfully implementing e-government in Zambia by considering citizens ' and businesses ' perceptions on e-government. Further, the study investigates what interventions have been put in place to encourage e-government development. The motivation of the study is that despite huge investments in e-government, there has been relatively slow adoption rendering the said interventions not to culminate into meaningful so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…Though public sector digital transformation is viewed as a means of improving democracy, its implementations are saddled with sociotechnical challenges that go beyond just the introduction of technology [13]. Some of the challenges are identifying, knowing, and understanding user needs and expectations [17]; limited network infrastructure [28]; and finding approaches to deal with the complexities as well as contradictions in large public sector institutions taking into account the economic values and democratic benefits of the context [7], and extensive stakeholder engagement throughout digitalization [28].…”
Section: Public Sector Digital Transformationmentioning
confidence: 99%
“…Though public sector digital transformation is viewed as a means of improving democracy, its implementations are saddled with sociotechnical challenges that go beyond just the introduction of technology [13]. Some of the challenges are identifying, knowing, and understanding user needs and expectations [17]; limited network infrastructure [28]; and finding approaches to deal with the complexities as well as contradictions in large public sector institutions taking into account the economic values and democratic benefits of the context [7], and extensive stakeholder engagement throughout digitalization [28].…”
Section: Public Sector Digital Transformationmentioning
confidence: 99%
“…The EGDI shows that sub‐Saharan African (SSA) countries are the lowest‐ranked among 193 nations (Verkijika & De Wet, 2018). The challenges that affect the implementation of e‐government initiatives in the SSA region lead to diversified implementation strategies at various levels (Bwalya, Du Plessis, & Rensleigh, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Information preciseness, timeliness, and sufficiency were found to be the key measures in assessing the IQ of government e-services. Bwalya et al (2014) investigated the potential of successfully implementing e-government in Zambia by considering both citizens’ and businesses’ perceptions of e-government. Al-Soud et al (2014) showed that issues like privacy and security concerns, affordability, and acceptance appear to be the major challenges for adopting e-government services in Jordan, and thus more attention in designing, developing, and implementing such services is required in this context.…”
Section: Introductionmentioning
confidence: 99%